Pt-Fe3O4, Pd-Fe3O4, and Au-Fe3O4Nanoheterodimers and Their Efficacy as Radiosensitizers in Cancer Therapy - Klein, Stefanie; Otto, Julia; Harreiß, Christina; Distel, Luitpold; Leistner, Angelika; Neuhuber, Winfried; Spiecker, Erdmann; Kryschi, Carola (ACS Applied Bio Materials, 2021)
The X-radiation enhancing effect of caffeic acid-functionalized Au-Fe3O4, Pt-Fe3O4, and Pd-Fe3O4 nanoheterodimers (NHDs) on 2D and 3D breast tumor (MCF-7) and healthy breast epithelial (MCF-10A) cells was comprehensively examined by performing cell viability, reactive oxygen species (ROS) detection, enzyme activity, and clonogenic assays. Intracellular NHDs were observed to cause DNA fragmentation and to enhance superoxide and hydroxyl radical formation in MCF-7 cells when exposed to a single dose of 1 Gy. MCF-7-derived multicellular tumor spheroids (MCF-7 MCTS) and MCF-10A-derived multicellular spheroids (MCF-10A MCS) were incubated with the NHDs and irradiated with five daily doses of 2 Gy. The Au-Fe3O4 and Pt-Fe3O4 NHD-loaded MCF-7 MCTS significantly decreased in volume after being exposed to fractionated irradiation, whereas intracellular Au-Fe3O4 and Pt-Fe3O4 NHDs promoted the growth of the irradiated MCF-10A MCS. Moreover, Au-Fe3O4 and Pt-Fe3O4 NHDs were shown to impede ROS formation and inhibit DNA strand breakage in the noncancerous MCF-10A cells. On the other hand, the Pd-Fe3O4 NHDs boosted X-radiation-induced damage of MCF-10 A cells, which was ascribed to impairment of the ROS scavenging enzyme activities. In summary, caffeic acid-functionalized Au-Fe3O4 and Pt-Fe3O4 NHDs performed as excellent X-radiation enhancing agents in breast tumor cells, while they protect healthy breast epithelial cells against X-radiation.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Au-Fe; caffeic acid; MCF-10A; MCF-7; multicellular tumor spheroids; Pd-Fe; Pt-Fe; radiotherapy